Research on heavy metal accumulation of Cu, Pb, Cd and Zn of the carrot - Son, N. H.; Huong, B. T. L.; Ka, T. T. (International Journal of Agricultural Technology, 2015)
The researching results of Cu, Pb, Zn and Cd accumulation ability of the carrot (Daucus carota subsp. Sativus) showing that these metals are accumulated mainly in the leaves accounting for 66-91% of the total metal accumulated content. The highest accumulating concentrations of Cu in roots is 0.532 mg/kg, in leaves is 1.342 mg/kg in the condition that the soil is affected at 100 mg/kg. The highest accumulation of Pb concentrations in the roots is 0.274 mg/kg, in leaves is 0.853 mg/kg at the Pb concentration in experimental soil of 140 mg/kg. The highest accumulation of Zn concentrations in roots is 14.35 mg/kg, in leaves is 22.136 mg / kg at the experimental concentrations of 400 mg/kg. The highest accumulation of Cd in roots is 0.0293 mg/kg and in leaves is 0.085 mg/kg at the Cd concentrations in the soil of 4 mg/kg. In general, the highest accumulating concentrations of heavy metals in plants grown on soil which gets heavy metals infection 02 times higher than QCVN 03: 2008 / BTNMT. At higher experimental concentrations, plants have the signs of retardation, the accumulating concentration in plants is decreased.